An overview of the anthropological theories - Mohamad Diah, Nurazzura; Hossain, Dewan Mahboob; Mustari, Sohela; Ramli, Noor Syafika (Centre for Promoting Ideas, USA, 2014)
Theories are treated as the lifeblood of the disciplines like sociology and anthropology. As a newer discipline that has grown approximately over the last two hundred years, anthropology has proposed different important theories on man and culture. This article presents with an overview of the theories of anthropology developed over the last two hundred years. This can be considered as a general summarized reading of the important anthropological theories like evolutionism, diffusionism, historical particularism, functionalism, culture and personality, structuralism, neo-evolutionism, cultural ecology, cultural materialism, postmodernist and feminist explanations. This article concludes that though each of these theories was criticized by the subsequent theorists, all these theories contributed a lot in the development of anthropology as a discipline.